Pautas para el examen de patentes sobre anticuerpos monoclonales - Juan Correa; Catalina de la Puente; Ramiro Picasso; Constanza Silvestrini (South Centre, 2024)
– The objective of this research is to learn about the status of patent applications for monoclonal antibodies (mAbs). The paper analyzes the different claim strategies used by applicants to obtain patent protection. The database constructed and described in South Centre Research Paper No. 186 was used as a source of information. The main claims used in the field of mAbs, the type of IPC classification and the type of invention (product or process) most frequently used in patents granted in force or expired in Argentina were investigated. Finally, the use of the Argentine patenting guidelines in the case of mAbs is analyzed and recommendations are made regarding possible additions to the patentability guidelines.
Keywords: 300; Patentrecht; Medizin; Argentinien